2002
DOI: 10.1046/j.1365-3180.2002.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Do maize cultivars demonstrate tolerance to the parasitic weed Striga asiatica?

Abstract: Summary Three cultivars of maize (TMV‐1, Katumani and Staha) were grown in the absence and presence of the root hemiparasite Striga asiatica in the field in eastern Tanzania. Infested Katumani and TMV‐1 plants yielded 22% and 25% less grain than uninfested plants; however, the grain yield of Staha was similar in both infested and uninfested plants. Measurements of gas exchange and the quantum yield of photosystem II (ΦPSII) revealed that photosynthesis and stomatal conductance were lower in infested plants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
4
37
1
1
Order By: Relevance
“…In the evaluations which took into account the presence and absence of Striga, the sorghum cultivar Ochuti tolerated Striga in Kenya (Gurney et al, 1995). Similar findings were obtained in the maize cultivar Staha in Tanzania (Gurney et al, 2002), maize genotypes CG4141 and R201 (Musambasi, 1997;Mabasa, 2003) in Zimbabwe, a land race sorghum cultivar, Tiemaringfing in Mali (Ast et al, 2000), the following sorghum varieties KSV-4, NR71150 and NR71182 when 50 to 250 kg / ha Nitrogen (N) was added.…”
Section: Introductionsupporting
confidence: 66%
“…In the evaluations which took into account the presence and absence of Striga, the sorghum cultivar Ochuti tolerated Striga in Kenya (Gurney et al, 1995). Similar findings were obtained in the maize cultivar Staha in Tanzania (Gurney et al, 2002), maize genotypes CG4141 and R201 (Musambasi, 1997;Mabasa, 2003) in Zimbabwe, a land race sorghum cultivar, Tiemaringfing in Mali (Ast et al, 2000), the following sorghum varieties KSV-4, NR71150 and NR71182 when 50 to 250 kg / ha Nitrogen (N) was added.…”
Section: Introductionsupporting
confidence: 66%
“…The ability to maintain high rates of CO 2 -assimilation as mechanism to endure parasite infection was earlier reported by Gurney et al (2002). They also suggested that CO 2 -assimilation could be used as a screening measure for tolerance.…”
Section: Co2 Assimilationmentioning
confidence: 61%
“…The latter cause reduced stomatal conductance, one of the reasons for reduced CO 2 -assimilation of infected hosts (Prabhakara Setty and Hosmani 1981;Press and Stewart 1987;Graves et al 1989;Gurney et al 1995;Smith et al 1995;Gurney et al 1999). CO 2 -assimilation of Striga infected host plants is further negatively affected through a reduced efficiency of the photosynthetic apparatus (Gurney et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different measures of tolerance have been proposed, ranging from host plant damage scores to yield, yield loss, or relative yield loss under Striga infestation (Efron, 1993;Kim, 1994;Adetimirin et al, 2000b;Gurney et al, 2002;Kim et al, 2002). None of these measures account for the difference in resistance among genotypes and hence they ignore the fact that the observed damage is due both to Striga infection level (resistance) and the extent to which the specific genotype endures these infections (tolerance).…”
Section: Introductionmentioning
confidence: 99%